Giant Cell Arteritis: Clinical Guide for the Eyecare Professional - Kress, William D; Neal, John M (Canadian Journal of Optometry, 2019)
Purpose The purpose of this article is to review giant cell arteritis, with a focus on ophthalmic manifestations, and provide a quick reference for clinical identification, diagnosis and appropriate management. Summary Giant cell arteritis is one of a few true medical emergencies that may present initially to the eyecare professional. Understanding the clinical picture of disease course and management arms the eyecare professional with the ability to detect and manage early in the disease process, potentially preventing blindness and life-threatening systemic manifestations.